Islamic Education in Al-Islam Kemuhammadiyahan to ‎Prevent the Culture of Shirk on Social Media ‎ - Abdul Azis; Ridho Riyanto; Eko Tuanto; Suradiyono; Mhd. Lailan Arqam (State Islamic Institute of Madura, 2023)
The development of social media or information media also has two sides that affect to each other positive or negative. Behavior that depends on social media needs, to forget the creator where these actions are included as a culture of shirk in seeing the sophistication of social media. The efforts of Al-Islam Kemuhammadiyahan (AIK) in higher education can provide innovative solutions in overcoming the cultures of shirk towards social media culture that has become a sense of addiction to the sophistication of social media. This research uses literature study research, where the process of collecting data from books or journal articles that are in accordance with the subject of research, namely about Islamic anthropology in AIK to prevent shirk culture in social media. The result of this study is that AIK can prevent the culture of shirk in social media by increasing the hours of faith courses. This is so that students are able to choose and filter what content can make themselves better in their religious knowledge so that they can stay away from content that contains shirk. In addition, there is an information fiqh course, so that students know the Islamic view of social media, are able to use social media wisely in accordance with Islamic views, students are able to filter incoming information and students’ tabayyun incoming information and are able to disseminate good information that does not contain shirk.